FACTORS INFLUENCING STUDENTS CHOICE OF FAST FOOD RESTAURANTS - Blešić, Ivana; Popov-Raljić, Jovanka; Pivac, Tatjana; Ivkov, Milan (Economics of Agriculture, 2018)
The global expansion of fast food consumption habits and the consequent change in the competitive environment led to greater market research and the targeting of consumer groups. On the other hand, the growth of the market and the increase in the number of fast food restaurants have encouraged consumers to pay more attention to the products they consume, that is, have influenced their interest in the diversity of factors that are decisive when choosing a restaurant. This study investingates factors influencing students choice of fast food restaurants. The study was conducted at University of Novi Sad. The results show that the most important influences on this choice are Food Quality, Nearness and Accessibility and Hygienic factors, primarily cleanliness of the restaurant, kitchen, and service personnel. Differences in fast food choice factors were found regarding the gender of respondents.